Conventional and Innovative Metaphors with Source Sphere “Liquidity” in English Investment Discourse - A. E. Buzheninov (Научный диалог, 2022)
The results of the metaphorical model study “investment phenomenon is a liquid” in the investment English discourse are presented. The relevance of the study is due, on the one hand, to the most important epistemological role of metaphor as a mechanism that categorizes, interprets and forms knowledge about the world and its phenomena, and on the other hand, the fact that the study of the metaphorical model is carried out on the basis of scientific discourse. The methodological basis of the study is the frame-slot analysis of the metaphorical model, which includes contextual, component and definitional types of analysis of the metaphorically used lexical units. A review of works devoted to various aspects of the study of conventional and innovative metaphors is given. The work develops a frame-slot structure of the metaphorical model under study, which is represented by such frames as “Movement of a liquid” (slots: “Vessels”, “Reservoirs”), “Disasters” and “Procedural properties of a liquid”. Particular attention is paid to the role of conventional and innovative metaphors in the conceptualization of investment phenomena. The derivative nature of innovative metaphors from conventional ones is shown, the first ones represent a further expansion of the conceptual links between the target sphere and the source sphere by occasional lexical filling of the target slots.